Fire structural resistance of basalt fibre composite. (April 2015) - Bhat, T.; Chevali, V.; Liu, X.; Feih, S.; Mouritz, A.P.
Abstract: Basalt fibres are emerging as a replacement to E-glass fibres in polymer matrix composites for selected applications. In this study, the fire structural resistance of a basalt fibre composite is determined experimentally and analytically, and it is compared against an equivalent laminate reinforced with E-glass fibres. When exposed to the same radiant heat flux, the basalt fibre composite heated up more rapidly and reached higher temperatures than the glass fibre laminate due to its higher thermal emissivity. The tensile structural survivability of the basalt fibre composite was inferior to the glass fibre laminate when exposed to the same radiant heat flux. Tensile softening of both materials occurred by thermal softening and decomposition of the polymer matrix and weakening of the fibre reinforcement, which occur at similar rates. The inferior fire resistance of the basalt fibre composite is due mainly to higher emissivity, which causes it to become hotter in fire.